2014
DOI: 10.1126/science.1254070
|View full text |Cite
|
Sign up to set email alerts
|

The environmental controls that govern the end product of bacterial nitrate respiration

Abstract: In the biogeochemical nitrogen cycle, microbial respiration processes compete for nitrate as an electron acceptor. Denitrification converts nitrate into nitrogenous gas and thus removes fixed nitrogen from the biosphere, whereas ammonification converts nitrate into ammonium, which is directly reusable by primary producers. We combined multiple parallel long-term incubations of marine microbial nitrate-respiring communities with isotope labeling and metagenomics to unravel how specific environmental conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
276
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(313 citation statements)
references
References 31 publications
10
276
4
2
Order By: Relevance
“…S1A and SI Results and Discussion). Various forms of OCCs have been linked to assimilatory or dissimilatory nitrite reduction in other organisms (2,45). Intriguingly, N. moscoviensis might link nitrite reduction to ammonia by the OCC with energy conservation by proton translocation across the cell membrane (SI Results and Discussion).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A and SI Results and Discussion). Various forms of OCCs have been linked to assimilatory or dissimilatory nitrite reduction in other organisms (2,45). Intriguingly, N. moscoviensis might link nitrite reduction to ammonia by the OCC with energy conservation by proton translocation across the cell membrane (SI Results and Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Based on genomic and experimental data from Nitrospira moscoviensis representing the ubiquitous Nitrospira lineage II, we identified ecophysiological traits that contribute to the ecological success of Nitrospira. Unexpectedly, N. moscoviensis possesses genes coding for a urease and cleaves urea to ammonia and CO 2 . Ureolysis was not observed yet in nitrite oxidizers and enables N. moscoviensis to supply ammonia oxidizers lacking urease with ammonia from urea, which is fully nitrified by this consortium through reciprocal feeding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to autotrophic anammox bacteria, heterotrophic denitrification bacteria are apparently more active and responsive to organic-rich environments such as flooded soils and sediments . Furthermore, previous studies have found that a relatively low C/N ratio is favored to denitrification while the opposite is true for anammox (Tiedje et al, 1982;Schmidt et al, 2011;Kraft et al, 2014). Due to the frequent N fertilizer application in agriculture, the paddy soils system received much more N input than marine system and resulted in a low C/N value, which might explain the reason of denitrification over anammox in paddy soils.…”
Section: Anammox and Denitrification Activity In The Three Paddy Soilsmentioning
confidence: 94%
“…DNRA are less understood than denitrification although it can be a significant or even a dominant process in some ecosystems, [25]. Conditions favouring DNRA may include high temperature [26] and high C/N ratio, [27]. [28].…”
Section: Eqmentioning
confidence: 99%